2018
DOI: 10.1111/bcpt.13036
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Caffeine on Behavioural and Cognitive Deficits in Rats

Abstract: There are many studies that have sought to find drug therapies to prevent harm arising from sepsis. Such studies have represented a progress in the support to septic patients and also in the development of new pharmacological alternatives. Our interest was to investigate the caffeine effect on sepsis behavioural and memory impairments. Male rats were anaesthetized and the surgery was made to allow exposure of the caecum, which was then squeezed to extrude a small amount of faeces from the perforation site, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…Research in animal models indicates that caffeine can ameliorate cognitive decline [17]. Studies assessing possible mechanisms underlying this effect have suggested that the effects of caffeine on A 2A receptors can control abnormal synaptic plasticity and synaptotoxicity [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Research in animal models indicates that caffeine can ameliorate cognitive decline [17]. Studies assessing possible mechanisms underlying this effect have suggested that the effects of caffeine on A 2A receptors can control abnormal synaptic plasticity and synaptotoxicity [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Caffeine may also reinforce muscular activity and enhance recognition in patients with neurocognitive deficits (Assis et al 2018). Studies with humans have corroborated improvements in performance at work or in sports (Burke, 2008;Cappelletti et al 2015).…”
Section: Perspectives For the Clinical Use Of Caffeinementioning
confidence: 99%
“…They concluded that chronic caffeine consumption induces behavioral effects similar to those of anxiety, through antagonism of the adenosine A1 and A2 receptors. One of the most contrasting effects of caffeine involves cognition or memory improvement, which is reflected in a greater capacity for attention and enhanced problem-solving (Assis et al 2018). Studies with humans have demonstrated that doses of 0.5-4 mg kg-1 increase cognition by improving performance in problem-solving in working environments in a manner considered dose-dependent (McLellan et al 2016).…”
Section: Anxiogenic Effectmentioning
confidence: 99%
“…Cognitive defects that may be analogous to those present in patients with sepsis have been identified following CLP in rodents. These abnormalities have been attributed to a number of underlying causes, including neuroinflammation, a number of different brain regions, most notably the hippocampus and basal forebrain, and in some cases have been amenable to treatment [28,168,[222][223][224][225][226][227][228][229][230][231]. However, the relevance of these abnormalities to human sepsis is unknown.…”
Section: What Is Knownmentioning
confidence: 99%